A randomized pilot study comparing the role of PEEP, O2 flow, and high-flow air for weaning of ventilatory support in very low birth weight infants - Chang-Yo Yang; Mei-Chin Yang; Shih-Ming Chu; Ming-Chou Chiang; Reyin Lien (Elsevier, 2018)
Background: There is a lack of evidence to guide step-wise weaning of positive pressure respiratory support for premature infants. This study sought to compare the efficacy of three weaning protocols we designed to facilitate weaning of very low birth weight (VLBW, less than 1500 g) preterm infants from nasal continuous positive airway pressure (NCPAP) support. Methods: This was a prospective, randomized, controlled trial of VLBW preterm infants who received positive pressure ventilatory support in our neonatal intensive care unit (NICU) from April 2008 through March 2009. When these infants were weaned to CPAP as their last step of respiratory support, they would be randomly assigned to one of the following three groups as their further weaning methods (M): (M1) CPAP group, (M2) O2 flow group, and (M3) air flow group. The time period they needed to wean off any kind of respiratory support, as well as the likelihood of developing relevant prematurity related morbidities, were compared among patients using different weaning modalities. Results: 181 patients were enrolled in the study. Their gestational age (GA) and birth weight (BW) were 29.1 ± 2.5, 28.7 ± 2.4, 28.7 ± 2.4 (mean ± SD) weeks and 1142 ± 232, 1099 ± 234, 1083 ± 219 g, in M1, M2 and M3, respectively. The time (period) needed to wean off support was 16.0 ± 10.0 days (M1), 11.6 ± 6.4 days (M2), and 15.0 ± 8.9 days (M3), respectively (p = .033). Incidence of retinopathy of prematurity (ROP) and bronchopulmonary dysplasia (BPD) were both significantly higher in the O2 flow group (p = .048). Conclusions: Although using low oxygen flow significantly shortens CPAP weaning time, it may increase risks of BPD and ROP, both known to be related to oxygen toxicity. Unless the infant has BPD and is O2-dependent, clinicians should consider using air flow or just splinting with no support at all when weaning NCPAP. Key Words: weaning, nasal continuous positive airway pressure, very low birth weight, nasal air flow